The touristic values of Jordan pavilion at Expo 2020 Dubai and its most prominent challenges from visitors’ standpoint - Malkawi, Suad Fayez (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to identify the tourism reality of Jordan pavilion at Expo 2020 Dubai and its most prominent challenges from the point of view of visitor. The study used the analytical descriptive method and a questionnaire filled by a sample of 135 visitors The results showed that The tourism reality and its challenges in the Jordanian pavilion participating in Expo 2020 Dubai from the point of view of its visitors, in general, came as a whole with a moderate degree, the arithmetic Average was (1.80) with a standard deviation of (0.25), and the arithmetic Average for the first domain as a whole was (1.82) with a deviation of (1.82). Standard (0.250) with a moderate degree. While the arithmetic mean for the second field as a whole was (1.67), with a standard deviation of (0.50), and with a moderate degree Also.Based on the results of the study, several recommendations were made by the researcher including the suggestion to study the possibility of reproducing the sustainable city model in Expo 2020 Dubai in Jordan and this for the importance it represents and the benefit it might bring to the country development. The recommendations also include the need for coordination between the government and private sectors in Jordan in a more organized and effective way that leads to excellence and success in the upcoming participations, finally, the study focused on the necessity for comprehensive tourism planning for the event, in full coordination between the Participating entities much before the opening day.
Keywords: Expo 2020; the Jordanian pavilion; the tourism reality